What Can Make the Difference Between Chronotypes in Sleep Duration? Testing the Similarity of Their Homeostatic Processes - Putilov, Arcady A.; Donskaya, Olga G. (Frontiers in Neuroscience, 2022)
The two-process conceptualization of sleep-wake regulation suggests that the biological underpinnings of the differences between morning and evening types in sleep timing and duration might be related to either the circadian process or the homeostatic process or both. The purpose of this report was to test whether morning and evening types might have similar homeostatic processes to achieve such ultimate goal of homeostatic sleep regulation as taking an adequate amount of sleep on free days. Weekend and weekday rise- and bedtimes reported for 50 paired samples of morning and evening types were averaged and simulated with a model of sleep-wake regulation. In morning and evening types of the same age, the homeostatic components of the sleep-wake regulation were found to be identical. Therefore, the difference in the circadian process between chronotypes of similar age can account for the observed differences between them in sleep timing and duration on weekdays and weekends. It was also demonstrated that the model-based simulations might have practical implications for informing an individual about the extent of unrecoverable reduction of his/her sleep on weekdays.